2020
DOI: 10.1186/s12974-020-01947-6
|View full text |Cite
|
Sign up to set email alerts
|

GM2 ganglioside accumulation causes neuroinflammation and behavioral alterations in a mouse model of early onset Tay-Sachs disease

Abstract: Background Tay-Sachs disease (TSD), a type of GM2-gangliosidosis, is a progressive neurodegenerative lysosomal storage disorder caused by mutations in the α subunit of the lysosomal β-hexosaminidase enzyme. This disease is characterized by excessive accumulation of GM2 ganglioside, predominantly in the central nervous system. Although Tay-Sachs patients appear normal at birth, the progressive accumulation of undegraded GM2 gangliosides in neurons leads to death. Recently, an early onset Tay-Sac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…6), including UDP-glucose ceramide glucosyltransferase (UGCG ), the enzyme converting ceramide to glucosylceramide, as well as β-galactosidase (GLB1), neuraminidase 1 (NEU1), and hexosaminidase α (HEXA), which convert gangliosides back to glucosylceramide. In addition to reduced concentrations of HexCer, the downregulation of these enzymes could theoretically lead to an accumulation of ceramides and GM1, -2, and -3 gangliosides, all of which have been identified as contributors of insulin resistance in various cell types (Demir et al 2020;Haynes et al 2012;Kajihara et al 2020;Lipina and Hundal, 2015;Sasaki et al 2018;Wang et al 2014;Yamashita et al 2003). However, ceramide concentrations were not significantly increased, possibly due to the observed downregulation of ceramide synthases.…”
Section: Discussionmentioning
confidence: 98%
“…6), including UDP-glucose ceramide glucosyltransferase (UGCG ), the enzyme converting ceramide to glucosylceramide, as well as β-galactosidase (GLB1), neuraminidase 1 (NEU1), and hexosaminidase α (HEXA), which convert gangliosides back to glucosylceramide. In addition to reduced concentrations of HexCer, the downregulation of these enzymes could theoretically lead to an accumulation of ceramides and GM1, -2, and -3 gangliosides, all of which have been identified as contributors of insulin resistance in various cell types (Demir et al 2020;Haynes et al 2012;Kajihara et al 2020;Lipina and Hundal, 2015;Sasaki et al 2018;Wang et al 2014;Yamashita et al 2003). However, ceramide concentrations were not significantly increased, possibly due to the observed downregulation of ceramide synthases.…”
Section: Discussionmentioning
confidence: 98%
“…NEU2 and NEU4 were shown to inhibit cancers 43 , 44 . NEU3 was reported to act as a pro-inflammatory mediator in the intestine and lung, but trigger inflammation in brain 45 47 . Besides NEU1 that has been decoded in this work, the roles of NEU2, NEU3, and NEU4 in CKD progression need to be explored in-depth in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The myelin sheath in the central nervous system is specifically formed in oligodendrocytes. In the previous study, we demonstrated that abnormal GM2 accumulation in the brain of Hexa−/−Neu3−/− mouse also causes the death of myelin-forming cells ( Demir et al, 2020 ). Here, our shotgun lipidomics data showed a significant decrease in the level of SMs in both the cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 99%